Mozambique - Lloyd, Robert B. (Countries at the Crossroads 2007: A Survey of Democratic Governance, 2007)
Countries at the Crossroads is an annual survey of government performance in 30 key countries worldwide that are at a critical crossroads in determining their political future. Crossroads provides a unique comparative tool for assessing government performance in the areas of accountability and public voice, civil liberties, rule of law, and anticorruption and transparency. The countries evaluated in Crossroads represent a range of governments: traditional or constitutional monarchies, one-party states or outright dictatorships, failed states, states where reforms have stalled or lagged behind, and states that suffer from insurgencies. The survey provides a comparative, in-depth assessment of democratic governance intended to help government officials, scholars, educators, nongovernmental organizations, and the media identify areas of progress and highlight points of concern. For the international community, the survey helps target diplomatic efforts and reform assistance. The narratives and scores clearly highlight the problems and successes of each government, and separate recommendations sections prioritize the steps that should be taken by the countries in question to remedy deficiencies in governance.
Keywords: G - Mozambique / Moçambique; L - english / inglês; governance / governação

Toward Gender Equality in Mozambique - Van den Bergh-Collier, Edda (Swedish International Development Cooperation Agency (SIDA), 2007)
This is an update of the previous Gender Profi le for Mozambique which was produced in 2000. Sida produces gender profi les for several countries with the purpose of providing a short and concise summary of the gender equality situation in partner countries. The profi e is a desk study reviewing and compiling available statistical material that may be of interest to anyone interested in women’s social, economic and legal position and understanding gender relations in Mozambique. The human development indicators show that signifi cant gender gaps exist in Mozambique. Thus a study of gender relations must repeatedly stress the relative deprivation of women in relation to men. The present profile emphasizes data that illustrates the relative position of men and women rather than attempting to capture and analyze gender relations in the whole country. A detailed discussion of gender relations for each thematic area would require extensive data and sociological/anthropological literature on the construction and dynamics of power relations between men and women in relation to that specifi c aspect of public and private life. For the most part, this kind of data is not available in Mozambique. Thus, the profile gives an overview of the types of issues women face as well as a brief indication of what is being done to address these challenges. Sida has developed generic terms of reference that identify specific issues and topics to be dealt with in individual country profi les. While the updated country profi le for Mozambique addresses all of the issues and topics described in the generic terms of reference, the data is presented in a specific sequence in order to more closely reflect the structure of the PARPA (Poverty Reduction Programme) and PES (Social and Economic Plan) of the Government of Mozambique. The PARPA and PES are central planning instruments for the Government; it is thus considered that this structure highlights potential linkages between Government priorities and Sida’s own development cooperation planning.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; gender / género; governance / governação; health / saúde; infrastructure - energy / infrastrutura - energia; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; land governance / gestão de terra; poverty / pobreza; youth / juventude

State Recognition and Democratization in Sub-Saharan Africa: A New Dawn for Chiefs? - Buur, Lars; Kyed, Helene Maria (Palgrave Macmillan, 2007)
State Recognition and Democractization in Sub-Saharan Africaآ explores the link between liberal-style democratization and state recognition of traditional authority in Sub-Saharan Africa. Being critical and empirically grounded, the book explores the complex, often counter-balancing consequences of the involvement of traditional authority in the wave of democratization and liberal-style state-building that has rolled over sub-Saharan Africa in the past decade. It scrutinizes how, in practice, traditional leaders are being drawn into governance in Mozambique, Zambia, Namibia, Malawi, Burkina Faso, and the Somali region of Ethiopia, and relates these developments to state governance in the declining democracy of Zimbabwe and the emerging state of Northern Somalia.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; authority / autoridade; decentralization / descentralização; governance / governação

Governance, management and performance in health and education facilities in Bangladesh: findings from the Social Sector Perforamnce Qualitative Study - Oxford Policy Management (Oxford Policy Management, 2007)
This report presents findings from the Social Sector Performance Qualitative Study (SSPQS). The SSPQS was designed as a follow-up to the Social Sector Performance Surveys (SSPS), which were public expenditure tracking surveys undertaken in the primary and secondary education and government health and family planning systems between 2004 and 2006. In many respects, the SSPS findings were positive, documenting that systems of health and education service provision were functioning. While there were problems, including of corruption or leakage and poor quality services, the provision of health and education services was found to be reasonably effective within their given goals and resource constraints. The SSPQS was designed to use qualitative methods to triangulate, explore and illustrate selected findings from the SSPS. The research on schools drew on the Heneveld-Craig framework for analysing school effectiveness. Applied here, this entailed a focus on understanding how the quality of supporting inputs (parental and community participation, supervision and material inputs) and enabling conditions (the effectiveness of school management and the incentives of teachers), relate to the quality or performance of the facility. To explore the governance of schools and health facilities, the research also drew on the analytical framework developed in the World Development Report 2004 to unearth accountability mechanisms linking users, providers and policy makers. The main findings of the report are presented in Sections 3 to 5.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Northern PEA; education / educação; governance / governação; health / saúde